The quest for a shared identity in a composite monarchy: Review on Le royaume inachevé des ducs de Bourgogne by Élodie Lecuppre-Desjardin - Stein, Robert (BMGN - Low Countries Historical Review, 2017)
In 1473 Charles the Bold made his famous entry in the town of Trier toimpress Emperor Frederic iii with his astonishing wealth, and to convincehim to promote his lands into the double kingdom of Friesland-Burgundyas one of the parts of the Holy Roman Empire. Although this was not thefirst time the Burgundian dukes of the house Valois became associated with a kingdom of their own, it was certainly the closest they ever came to the realisation of their dream. When I started to read Le royaume inachevé des ducs de Bourgogne (XIVe-XVe siècles) (Paris 2016), I expected Charles’s endeavor to lie at the heart of the argument, but this is not the case. Only five of the ca. 350 pages have been devoted to the Trier episode. Essentially, this book deals with another, equally interesting question, namely the question of the coherence of the Burgundian lands. This article is part of the discussion forum 'Constructing and Deconstructing the ‘State’: the Case of the Low Countries'.